FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM MENGIKUTI ORGANISASI BADAN EKSEKUTIF MAHASISWA DI FKIP UNIVERSITAS RIAU - Deniro, Roberto Edo; Hambali, Hambali; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract:This research is motivated by the lack of student’s interest in participating in student organizations, through research conducted on students of the Faculty of Teacher Training and Education (FKIP), most students think that organizing will only add to the routine that makes students less than optimal in carrying out the obligations of the learning process in the classroom, even though departing from this, student organizations are a forum that is able to grow a credible character through positive activities carried out by student organizations so as to form a bright, competent generation, to build the nation in the future. Formulation of the problem in this research is about the factors that influence student interest in joining the student executive board organization at FKIP Universitas Riau. The purpose of this research is to find out the factors that influence student interest in joining the student executive board organization at FKIP Universitas Riau. The sample in this study was taken using a purposive sampling technique. This research method is descriptive quantitative. The data collection instrument used in this study is a questionnaire consisting of 2 indicators with 14 questions, which will then be analyzed using the percentage analysis technique method. . From the results of the study, it can be seen that external and internal factors that influence FKIP students in joining the Student Executive Board organization at FKIP Universitas Riau,It can be concluded that the answer strongly agrees with the percentage of 39.4% plus the answer agrees with an average percentage of 52.65% totaling 92.05%, according to the benchmark it is in the range of 75.01% - 100%. So the factors that influence the interest of FKIP students in participating in the Student Executive Board organization at FKIP Universitas Riau can be said to be "Very High"Key Words: Interests, Students, Student Organizations.